Influence of viscosity and amine content on CC conversion and color stability of experimental composites. Issue 5 (May 2015) - Camargo, Fernanda Missio; Della Bona, Álvaro; Moraes, R.R.; Coutinho de Souza, C.R.; Schneider, Luis Felipe
Highlights The degree of CC conversion was dependent on the CQ:amine. The influence of viscosity on DC was dependent on the CQ:amine ratio. The CQ:amine ratio had a significant influence on the yellow–blue axis data. The overall color stability was only affected by the CQ:amine ratio. The overall color stability was not affected by the materials' viscosity.